2004
DOI: 10.1158/0008-5472.can-04-0143
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil and Its Derivative Trigger Apoptosis through Glutathione Extrusion by Multidrug Resistance Protein MRP1

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 30 publications
12
121
1
2
Order By: Relevance
“…Therefore, a subsequent increase in cellular doxorubicin concentration by indomethacin may have partly played a role. Other mechanisms by which indomethacin might induce apoptosis are increased glutathione extrusion mediated by MRP1 (Trompier et al, 2004) or increased ATP consumption by MRP1 ATPase activity in analogy to the observed verapamil-induced ATP consumption in P-glycoprotein-overexpressing cells (Broxterman et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, a subsequent increase in cellular doxorubicin concentration by indomethacin may have partly played a role. Other mechanisms by which indomethacin might induce apoptosis are increased glutathione extrusion mediated by MRP1 (Trompier et al, 2004) or increased ATP consumption by MRP1 ATPase activity in analogy to the observed verapamil-induced ATP consumption in P-glycoprotein-overexpressing cells (Broxterman et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…37 Pharmacological activation of MRPs induces apoptosis by GSH depletion. 38 In clear contrast, other studies have shown that inhibition of MRPmediated transport accelerates apoptosis. 20,21 Conversely, overexpression of MRP proteins inhibit cell death induced by death receptor activation and cytotoxic drugs.…”
Section: Figure 1 Apoptotic Signaling Pathways (See Text For Further mentioning
confidence: 93%
“…However, the calcium channel blocker verapamil and its derivative NMeOHI2, in addition to the several non-steroidal anti-inflammatory drugs (e.g., indomethacin), have shown collateral sensitivity toward MRP1 overexpressing cells [191,192] . These agents were proposed to trigger apoptosis in cells overexpressing MRP1 via intracellular GSH depletion.…”
Section: Examples Of Such Inhibitors Are Cyclosporine a [26184-187]mentioning
confidence: 99%